Деякі аспекти забезпечення прав підозрюваного під час застосування запобіжних заходів - Фоміна, Т. Г.; Fomina, T. H.; Тетяна Фоміна (Право і безпека. - 2015. - № 1 (56). - С. 65-71., 2015)
Наведено перелік запобіжних заходів згідно з кримінальним процесуальним законодавством України. Визначено засоби забезпечення прав підозрюваного під час їхнього застосування. Окремо досліджено обов’язки слідчого, прокурора, слідчого судді під час вирішення питання про застосування запобіжних заходів. Указано на недоліки нормативної регламентації. У зв’язку з тим запропоновано певні напрямки удосконалення процесуального законодавства України.

Persons involved in criminal proceedings as suspects and defendants suffer significant limitations of the rights. Due to this fact the special urgency are the issue of guaranteeing their rights during criminal proceedings, and especially while using the preventive measures. The duties of an investigator, prosecutor, investigating judge while taking the decision on using preventive measures are studied in the article. It is indicated that an important way to guarantee the rights of the suspect is a requirement of the law to an investigator and prosecutor to initiate preventive measure, if there are relevant reason, because it is important for the suspect, which of the listed grounds provided an investigator, prosecutor, investigating judge the right to limit his rights. At the same time it is stressed that it is not enough only to state the reason for using preventive measures. It is necessary that these grounds are confirmed by relevant materials of the criminal proceedings. Besides, the duty of an investigating judge to consider all the circumstances affecting the choice of preventive measure is studied. It is indicated that the law provides provisions for giving the copies of the motion and materials for the suspect, which ground the need for preventive measure or its change. However, the Code does not state, who must hand a copy of the motion and indicated materials. Therefore, the author has offered to put this responsibility on the person who issued the motion (prosecutor or investigator), and therefore the part 2 of the Art. 184 and the part 3 of the Art. 200 of the Criminal Procedural Code of Ukraine should be clarified. Besides, in order to improve the provisions on guaranteeing the rights of the suspect it is suggested to amend the point 7 of the part 2 of the Art. 193 of the Criminal Procedural Code of Ukraine concerning the clarification to the suspect, the accused the right to file a motion to change the preventive measure. Consolidation of the relevant provisions in the current legislation, of course, will contribute to guaranteeing the rights of the suspect.

Приведён перечень мер пресечения согласно уголовному процессуальному законодательству Украины. Определены средства обеспечения прав подозреваемого при их применении. Отдельно исследованы обязанности следователя, прокурора, следственного судьи при решении вопроса о применении мер пресечения. Указано на недостатки нормативной регламентации. В связи с тем предложено определенные направления совершенствования процессуального законодательства Украины.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Кримінально-процесуальний кодекс України; Criminal Procedural Code of Ukraine; УПК Украины; досудове розслідування; запобіжні заходи; забезпечення прав підозрюваного; підозрюваний; pre-trial investigation; preventive measures; guaranteeing the rights; suspect; досудебное расследование; меры пресечения; обеспечение прав подозоеваемого; подозреваемый